1977
DOI: 10.1111/j.1399-3054.1977.tb04881.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Sea Water and Temperature on the Germination Behaviour of Crithmum maritimum

Abstract: The seeds of Crilhmum maritimum L. were germinated fioating on various concentrations of sea water up to 50% at constant temperatures of 5, 10, 15, 20, and 25°C and at alternating temperatures of 5 and 15°C, 5 and 25°C, and 15 and 25°C. Significantly higher germination was obtained at alternating than at constant temperature. When two constant temperatures at which no germination occurred were alternated, good germination was obtained. There was reduced germination and increase in time of first germination as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…Sea fennel seeds response to salinity has been reported by Okusanya (1977) and Marchioni-Ortu and Bocchieri (1984). Our results confirmed some of the results of these studies, showing that salinity inhibited germination even at low concentrations.…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…Sea fennel seeds response to salinity has been reported by Okusanya (1977) and Marchioni-Ortu and Bocchieri (1984). Our results confirmed some of the results of these studies, showing that salinity inhibited germination even at low concentrations.…”
Section: Discussionsupporting
confidence: 95%
“…Conversely, salt pretreatment did not affect Plantago crassifolia L. seed germination, at any salt concentration (Vicente et al 2004). In our work, germination of sea fennel seeds started on the 18th day of incubation in distilled water, in good agreement with Okusanya (1977). However, our results differed from those of Marchioni-Ortu and Bocchieri (1984), who showed that Sardinian seeds germinated on the 5th day of setting.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Another adaptation to salinity is the increase in succulence, which reduces the concentration of salts in the protoplasm (Ghoulam et al 2002). The greater growth of the roots in comparison with the aerial part is also considered an adaptation to saline stress (Alshamary et al 2004) since it results in an increased surface area for water uptake, thereby preventing dehydration (Okusanya 1977). Salinity reduces the uptake and transport of nitrate (Carillo et al 2005;Surabhi et al 2008;MaaroufiDguimi et al 2011) and, consequently, the assimilation of nitrogen necessary for protein synthesis (Silveira et al 2001;Qu et al 2011).…”
Section: Introductionmentioning
confidence: 99%